The Effect of Android-Based Educational Games on Students' Cognitive Learning Outcomes in the Electrical Engineering Fundamentals Subject - Selpi Amanda Fadillah; Siswo Wardoyo; Suhendar Suhendar (International Journal of STEM Education for Sustainability, 2026)
The purpose of this study was to ascertain how using educational games based on Android affected students' learning results in the Electrical Engineering Fundamentals course, particularly with regard to fundamental cable connection procedures. This study included a nonequivalent control group design, a quasi-experimental method, and a quantitative methodology. 62 10th graders enrolled in a Vocational High School in Banten, Indonesia's Electrical Power Installation Engineering (TITL) program served as the subjects; 30 of them were in the control group and 32 were in the experimental group. Tests (pretest and posttest) and questionnaires were utilized as data collection methods. The research tool was tested for validity and reliability, and the results showed that it was suitable for usage. The average pretest and posttest scores rose from 55.00 to 74.00 in the control class and from 47.19 to 77.50 in the experimental class, according to the data. With a significance threshold of 0.000 0.05, the paired sample t-test revealed a calculated t-value of -14.827 for the control class and -18.735 for the experimental class, showing a substantial improvement in learning outcomes following the treatment. An average score of 0.89, classified as appropriate, was obtained through validation by media and material specialists. Therefore, it can be concluded that the use of Android-based educational games is effective and has a significant impact on improving student learning outcomes compared to conventional learning methods.